1995
DOI: 10.1074/jbc.270.25.14983
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of CTP Synthetase from Saccharomyces cerevisiae by Protein Kinase C

Abstract: Phosphorylation of CTP synthetase (EC 6.3.4.2, UTP:ammonia ligase (ADP-forming)) from Saccharomyces cerevisiae protein kinase C was examined. Using pure CTP by synthetase as a substrate, protein kinase C activity was dose- and time-dependent and required calcium, diacylglycerol, and phosphatidylserine for full activation. Protein kinase C activity was also dependent on the concentration of CTP synthetase. Protein kinase C phosphorylated CTP synthetase on serine and threonine residues in vitro whereas the enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
73
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 38 publications
6
73
0
Order By: Relevance
“…In addition, the kinetic analysis of the purified mutant enzymes revealed that the S36A and S354A mutations caused a decrease in the V max of the reaction. These results were consistent with previous data showing that protein kinase C phosphorylation stimulates the activity of the pure wild type CTP synthetase (33,35). Interestingly, the CTP synthetase activity in cells bearing the S330A mutant enzyme was elevated, and kinetic analysis of the purified enzyme showed that the S330A mutation caused an elevation in the V max of the reaction.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In addition, the kinetic analysis of the purified mutant enzymes revealed that the S36A and S354A mutations caused a decrease in the V max of the reaction. These results were consistent with previous data showing that protein kinase C phosphorylation stimulates the activity of the pure wild type CTP synthetase (33,35). Interestingly, the CTP synthetase activity in cells bearing the S330A mutant enzyme was elevated, and kinetic analysis of the purified enzyme showed that the S330A mutation caused an elevation in the V max of the reaction.…”
Section: Discussionsupporting
confidence: 82%
“…Regulation of this enzyme is critical because the product of its reaction CTP is essential for the synthesis of nucleic acids and membrane phospholipids (18). One of the mechanisms by which CTP synthetase activity is regulated in S. cerevisiae is by phosphorylation via protein kinase C (33,35). Protein kinase C is a lipid-dependent protein kinase required for S. cerevisiae cell cycle (74 -78) and plays a role maintaining cell wall integrity (79).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations